Synergistic enhancement of thermal conduction and microwave absorption of silica films based on graphene/chiral PPy/Al2O3 ternary aerogels. (31st October 2022) - Yang, Xiaofen; Fu, Kang; Wu, Lishan; Tang, Xi; Wang, Jinglin; Tong, Guoxiu; Chen, Dabo; Wu, Wenhua
Abstract: Severe problems of heat dissipation and electromagnetic (EM) interference are quite detrimental to modern electronics, prompting researchers to develop advanced integrated materials of thermal conduction, microwave absorption, and electrical insulation. However, their simultaneous improvement is restricted by some inevitable contradictions among them. Herein, we pioneered graphene (GN)/PPy/Al2 O3 ternary aerogels as an advanced membrane filler for a synergistic enhancement of thermal conduction, EM wave absorption, and electrical insulation. GN/PPy/Al2 O3 ternary aerogels are produced via a simple solution blending and vacuum freeze-drying process, and then filled into silica oils to form silica gel films via a hot-pressing process. A few thermal conduction-electric conductivity-type graphene and PPy (3–5 wt%) were uniformly dispersed in thermal conduction-electrical insulation-type Al2 O3 nanoparticles, forming multiple polarizations and constructing an effective heat-conducting but electrical-insulating pathway for phonon transmission. In this case, GN/PPy/Al2 O3 ternary aerogels (1:1:15, 50% loading) possessed a wide absorption frequency band (6.48 GHz, 2.0 mm thickness), high thermal conduction (4.649 W/(m·K)), and excellent electrical insulation ( σ  = 0.0282 S/m). Notably, their thermal conduction and microwave absorption abilities significantly outperform most reported fillers. This paper provides a simple and effective method for designing advanced thermal conduction-microwave absorption-electrical insulation integrated materials with great potential in modern electronics. Graphical abstract: A synergistic enhancement of thermal conduction, EM wave absorption, and electrical insulation in GN/PPy/Al2 O3 ternary aerogels by constructing an effective heat-conducting but electrical-insulating pathway for phonon/electron transmission. Image 1